JOB SATISFACTION OF EMPLOYEES WORKING IN INFORMATION TECHNOLOGY SECTOR (International Journal of Food and Nutritional Sciences, 2022)
Employees are the asset of every organization. Human resource is the important factor for many information technology companies for their growth. It depends on employee motivation, skill and quality of work. Job satisfaction is the level of contentment a employee has regarding his or her job. This feeling is mainly based on an individual’s perception of satisfaction can be influenced by a person’s ability to complete the required tasks